2017
DOI: 10.1093/qjmed/hcw231
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence of chronic subdural haematoma in the elderly

Abstract: The incidence of CSDH is much higher than previously reported. Reasons include a low threshold for imaging patients with recurrent falls and confusion, increasing use of anti-thrombotics and ageing population. In many older patients CSDH is a marker of underlying co-morbidities rather than a primary event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 21 publications
0
46
0
Order By: Relevance
“…Many studies, reported CSDH recurrence rate around 10-15% 3,8,13,17,25) and elderly patients had higher rate recurrence than younger ones 2,5,6,17) . In our series the recurrence rate in the elderly group was 20%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies, reported CSDH recurrence rate around 10-15% 3,8,13,17,25) and elderly patients had higher rate recurrence than younger ones 2,5,6,17) . In our series the recurrence rate in the elderly group was 20%.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CSDH using antithrombotic drugs, careful decision-making is compulsory, because these therapies are more common in non-traumatized CSDH patients with cerebrovascular and/or cardiovascular co-morbidities 20) . Furthermore, antiplatelet and anticoagulant drugs may increase the probability of CSDH recurrence as well as the VII factor deficit in young patients 2,8) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence rates of CSDH have been well described in higher-income regions of the world, and they demonstrate a positive correlation with increasing age; in a Japanese cohort, an incidence rate of 58 per 100,000 per year was noted in people above the age of 70 years, and a Welsh study reported an incidence rate of 273 per 100,000 per year in the population aged 95 years and above [4,5].…”
Section: Introductionmentioning
confidence: 92%
“…The overall incidence of CSDHs is estimated at 1.7 to 21 per 100 000 persons per year. 2,3 Throughout all the meninges, the subdural space is less tight and potentially vulnerable to trauma, when compared to the junctional layers of dura and arachnoid membrane. The layer of duraarachnoid interface, commonly designated as subdural space, is composed of the dural border cells.…”
Section: Introductionmentioning
confidence: 99%